Optimization of Gluten Free Cookies from Red and White Sorghum Flours - De Petre, N (2016)
The aim of this study was to evaluate the use of red/white sorghum flours in the development of gluten free cookies. A Box Behnken design involving guar gum (GG), baking powder (BP) and water added to a given formulation and red/white sorghum flours as categorical variable, was used to obtain the optimal gluten free cookie formulation. Resulting cookies were subjected to sensory evaluation being flavour, fragility and crispiness evaluated responses. After that, the optimal formulation was obtained being GG and BP significant variables whereas sorghum flour did not showed statistical significance. Also proximal composition, total phenols and antioxidant activity as 1,1-diphenyl-2-picrylhydrazyl (DPPH) sequestering activity were evaluated in optimized red (RSC) and white (WSC) sorghum cookies. In spite of being total polyphenols contents of RSC (280±1.83 mg tannic acid equivalents./100 g) higher than that from WSC (73±1.91 mg tannic acid equivalents /100 g), evaluated DPPH scavenging activity was important in both cookies. Consuming a portion (30g) of them would provide a DPPH scavenging capacity of 572 mg and 544 mg ascorbic acid equivalent from RSC and WSC, respectively, which could be compared to the one provide from a 100 g portion of strawberries. Resulting sorghum cookies would contribute to a more diverse and nutritious diet for celiac people.